A correlational study between the furniture use and arrangement in the dormitory bedrooms and the international relationship among the student residents - Sena, Mizraime Anne B. (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT This study investigated the correlation between furniture use and arrangement of dormitory bedrooms and the interpersonal relationships among the student residents. By definition itself, a correlational study simply determines if there is a systematic relationship that exists between the variables and does not infer causality or the relation between the cause and effect. In this study, the researcher used a correlational research design to determine the relationships of the variables, being the furniture use and arrangement in dormitory bedrooms and the interpersonal relationships among the student residents. A multi-stage sampling was adopted in selecting the respondents which composed of forty one residents representing all five different room arrangements in the dormitory. The researcher used survey, informal interviews, and observation sheets in gathering her data. The results of the data suggested that there exist a systematic relationship between the furniture use and arrangement of the bedrooms of Sampaguita Residence Hall and the interpersonal relationships of the student residents. It was found out that the room arrangement in terms of furniture position and distances of the beds and study tables which regulate interaction affect the relationship of the users in terms of their degree of closeness and interaction. To illustrate, the closer the furniture and the lesser the barriers between them suggested higher interpersonal relationships of the users. x The data gathered on furniture use also summarized that the bed is the most frequently used furniture in all the bedroom arrangements. This becomes significant because the closer the distances and the lesser the barriers between the beds where most activities were done imply higher degree of closeness and interaction between the student residents.